Rodinný dům - Diviš, Lukáš (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Téma bakalářské práce je rodinný dům. Jedná se o jednopodlažní dům částečně podsklepený. Suterén je obytný. Střecha je pultová se sklonem 7%. Jako nosné konstrukce byly použity obousměrné stěny Porotherm. Budova je osazená na mírně svažitém pozemku k směrem k západu. Všechny použité konstrukce odpovídají platným normám ČSN.

The topic of this bachelor thesis is a family house with one story above ground and residential basement under the part of building. Shed roof has a slope of 7%. As the load-bearing construction were used bidirectional structure walls made of Porotherm bricks. The building is situated on slightly sloping plot towards the west. All the used constructions are according valid ČSN regulations.
Family house
Keywords: Rodinný dům; sádrokartonová deska; cihelný blok; osazení do svahu; schodiště; skladba; tepelný most; podzemní podlaží; nadzemní podlaží; příčka; střecha; stříkaná tepelná izolace; Family house; plasterboard; brick block; fitting into the hillside; staircase; construction elements composition; thermal bridges; underground floor; above-ground floors; separation walls; roof; sprayed thermal insulation